Calcium intake of rural Gambian infants: a quantitative study of the relative contributions of breast milk and complementary foods at 3 and 12 months of age - Jarjou, L M A (Nature Publishing Group, 2012)
BACKGROUND/OBJECTIVES: There is a paucity of information from developing countries on total calcium intake during infancy, and potential consequences for growth and bone development. DESIGN: Observational longitudinal study of rural Gambian infants (13 males and 17 females) at 3 and 12 months of age. SUBJECTS/METHODS: Breast-milk intake and calcium concentration, weighed dietary intake, anthropometry, midshaft radius bone mineral content (BMC) and bone width (BW). RESULTS: At 3 and 12 months (mean±s.d.) calcium intake from breast milk was 179±53 and 117±38, and from other foods 12±38 and 73±105 mg/day. There was no difference in total calcium intake; 94% and 62% of calcium came from breast milk. At 3 and 12 months, weight s.d.-scores were −0.441±1.07 and −1.967±1.06; length s.d.-scores were −0.511±1.04 and −1.469±1.13. Breast-milk calcium intake positively predicted weight (P=0.0002, P⩽0.0001) and length (P=0.056, P=0.001). These relationships were not independent of breast-milk intake, which positively predicted weight (P⩽0.002) and length (P=0.06, P=0.004). At 3, but not 12 months, weight and length correlated with total calcium intake. There were no relationships between total calcium intake and breast-milk intake with BW or BMC. CONCLUSION: The combination of low calcium intake from breast milk and complementary foods resulted in a low total calcium intake close to the estimated biological requirement for bone mineral accretion. Relationships between calcium intake and growth were largely accounted for by breast-milk intake, suggesting that low calcium intake per se was not the limiting factor in the poor growth. These findings have potential implications for deriving calcium requirements in developing countries.